2016
DOI: 10.1590/1982-0194201600063
|View full text |Cite
|
Sign up to set email alerts
|

Acolhimento na atenção primária à saúde na ótica de enfermeiros

Abstract: Objective: To understand how the welcoming process occurs in the basic health units from the viewpoint of nurses. Methods: An exploratory study with a qualitative approach that used semi-structured interviews, and adopted the content analysis technique proposed by Bardin for data analysis. Results: Among the ten interviewed, nine were female. Analysis of the statements led to the emergence of access and the work process as empirical categories. Conclusion: Welcoming is performed in the Basic Health Units of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
17

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 2 publications
0
5
0
17
Order By: Relevance
“…Em outro estudo na literatura, a partir da visão de profissionais de saúde, evidenciou-se que ainda é predominante o trabalho nas unidades de saúde nos moldes tradicionais, centrados na consulta médica, na distribuição de fichas para demanda espontânea, sem de fato existir a resolução do problema do usuário não contemplando sua necessidade. Por isso, a importância do acolhimento, pois pode orientar e direcionar o atendimento apropriado à demanda apontada pelo usuário (CAMELO MS, et al, 2016).…”
Section: Discussionunclassified
“…Em outro estudo na literatura, a partir da visão de profissionais de saúde, evidenciou-se que ainda é predominante o trabalho nas unidades de saúde nos moldes tradicionais, centrados na consulta médica, na distribuição de fichas para demanda espontânea, sem de fato existir a resolução do problema do usuário não contemplando sua necessidade. Por isso, a importância do acolhimento, pois pode orientar e direcionar o atendimento apropriado à demanda apontada pelo usuário (CAMELO MS, et al, 2016).…”
Section: Discussionunclassified
“…Esse cenário deve ser transformado, pois a prática do acolhimento contribui na melhoria da (re)organização do serviço, visando ao atendimento da demanda espontânea nos serviços de saúde, sendo assim torna-se importante a implantação desse dispositivo de forma efetiva, pois ele possibilita o vínculo entre profissionais e usuários contribuindo também na qualidade do atendimento oferecido (CAMELO MS, et al, 2016). O acolhimento foi designado para colaborar com a qualidade dos sistemas de saúde possibilitando ao usuário acesso justo e integral no seu atendimento com a participação de multiprofissionais da saúde.…”
Section: Discussionunclassified
“…9 Patient embracement should be carried out by a multi-professional team, with the purpose of listening to the service user and identifying their needs so that care is as individualized as possible. 13,14 Based on adequate health professional training, patient embracement with risk classification can be carried out in parallel to programmed actions, increasing linkage and improving access to services. 9,14 The prevalence rates of actions aimed at women and at promoting healthy eating found by this study are compatible with those identified for the Midwest region.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Based on adequate health professional training, patient embracement with risk classification can be carried out in parallel to programmed actions, increasing linkage and improving access to services. 9,14 The prevalence rates of actions aimed at women and at promoting healthy eating found by this study are compatible with those identified for the Midwest region. The divergences found for the other promotion actions may be related to differences between the states the comprise the region, as well as to the methodology used to select the teams assessed.…”
Section: Discussionmentioning
confidence: 99%